2019
DOI: 10.1152/physrev.00036.2017
|View full text |Cite
|
Sign up to set email alerts
|

Sources of Vascular Nitric Oxide and Reactive Oxygen Species and Their Regulation

Abstract: Nitric oxide (NO) is a small free radical with critical signaling roles in physiology and pathophysiology. The generation of sufficient NO levels to regulate the resistance of the blood vessels and hence the maintenance of adequate blood flow is critical to the healthy performance of the vasculature. A novel paradigm indicates that classical NO synthesis by dedicated NO synthases is supplemented by nitrite reduction pathways under hypoxia. At the same time, reactive oxygen species (ROS), which include superoxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
314
0
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 400 publications
(325 citation statements)
references
References 1,087 publications
(1,227 reference statements)
3
314
0
8
Order By: Relevance
“…44 Hydrogen peroxide is an important diffusible second messenger that plays a functional role in intercellular signalling through gap junctions, connexins, and myoendothelial feedback. 45,46 H 2 O 2 mediates effects primarily through oxidation of cysteine thiols. In the endothelium, H 2 O 2 acts as a vasodilator and has been considered to be an endotheliumderived relaxing factor, effects that are induced largely through activation of PKG1a and posttranslational modifications involving S-glutathionylation.…”
Section: R Esum Ementioning
confidence: 99%
“…44 Hydrogen peroxide is an important diffusible second messenger that plays a functional role in intercellular signalling through gap junctions, connexins, and myoendothelial feedback. 45,46 H 2 O 2 mediates effects primarily through oxidation of cysteine thiols. In the endothelium, H 2 O 2 acts as a vasodilator and has been considered to be an endotheliumderived relaxing factor, effects that are induced largely through activation of PKG1a and posttranslational modifications involving S-glutathionylation.…”
Section: R Esum Ementioning
confidence: 99%
“…Research on the convoluted physicochemical properties of free radicals and NO is helpful in revealing the dual roles of RNS in redox signalling and oxidative stress. NO, a vital signalling molecule, has been well reviewed in previous reports, but it is striking to clarify how NO communicates information to achieve signal transduction. In organisms, NO is generated through a nitric oxide synthase (NOS) catalyzed reaction of L‐arginine.…”
Section: Cross‐talk Between Ros and Rnsmentioning
confidence: 99%
“…However, these results demonstrated that, in myocardial tissues of infarct area, IPA at 10 6 and 10 7 cfu/kg exhibited increase effects against oxidative stress. Oxidative stress refers to the process of oxidative damage caused by excessive ROS production, reduced scavenging capacity and an imbalance between the oxidation and antioxidant system (26). Nrf2 is an important transcription factor that is associated with regulating oxidative stress response.…”
Section: Discussionmentioning
confidence: 99%